Pengaruh Body Image dan Kecerdasan Emosi Terhadap Depresi Pada Remaja - Bestari, Aniq Ayu; Wahyuni, Zulfa Indira (‎‎‎TAZKIYA: Journal of Psychology, 2015)
This study was conducted to discover factors which affect teenage depression. Previous studiesindicate that there are gender effect, age of puberty, and psychological variables, body imageand emotion intelligence on teenage depression. Quantitative approach used in this studyusing multiple regression analysis. Sample of this study were 200 junior high school studentswho were chosen using non-probability sampling technique. In this study, researchersmodified data collecting instruments, Multidimensional Body-Self Relation Questionnaire-Appearance Scale, BarOn Emotional Quotient Inventory, and Beck Depression Inventory.Result of this study indicates that there are significant effects of body image, emotionalintelligence, gender, and age of puberty on teenage depression. Significant variables areappearance orientation, body size categorization, body image anxiety, and interpersonalability of emotional intelligence.